KOMUNIKASI TRANSENDENTAL PADA TAQWA, DZIKIR, DAN FALAH DALAM MAKNA SEMANTIK/MAJAZI - Muhtadin, Muhtadin (JURNAL PUSTAKA KOMUNIKASI, 2018)
The word "piety" comes from the word "waqaa-yaqii-wiqaayah" which means to maintain, and maintain. Takwa also means dodge, in this sense includes three aspects namely; (1). Shy away from the kufr attitude by believing in Allah SWT. (2). Attempt to carry out God's commandments and to know His prohibitions as optimally as possible (3). Ranging from all activities that distanced the mind from God .SWT. The word "dhikr" is essentially derived from the word "dzakara-yadzkuru-dzikran". Dzikir can also be interpreted by presenting into the mind of what was previously forgotten and this is a dhikr meaning "remember". The word dhikr can also be understood in the sense of "glory". The point is "Al-Qur'an". The basic meaning of "falah" is luck. The word falah when associated with the verses of the Qur'an is luck, salvation, and lasting in pleasure and goodness. This is reflected in the letter of Ali 'Imran verse 130, about the prohibition of usury. In this verse that ends with the warning of God, in order to be cautious of Him in order that people may be lucky. The one who justifies usury is threatened with the fire of hell. The Qur'anic concept of piety, dhikr, and falah is the same as the three money, in which these three concepts have the achievement of living in the heavens and the earthly life.